Caracterización de matrices de polivinil alcohol - alginato - quitosano - aloe vera - Echeverry Cuartas, Claudia Elena; Londoño, Martha Elena; Gómez Chabala, Luisa Fernanda (2021)
The purpose of this work was to obtain polymeric systems from Polyvinyl Alcohol (PVA), alginate and chitosan as possible matrix to encapsulate Aloe vera gel, seeking to integrate mechanical strength, biodegradability and biocompatibility of these polymers. In addition, Aloe vera gives the polymer matrix healing and emollient properties. Morphology, functional groups, mechanical properties and kinetic release behavior of the samples were evaluated. The matrices showed a morphology with interconnected pores and mechanical stability. The release of Aloe vera from the matrix of PVA-alginate-chitosan exhibited a non Fickian behavior, while alginate-chitosan presented a closer to Fickian behavior. PVA-chitosan-alginate and chitosan matrices, by their mechanical, morphological and interconnected and well defined pores, and alginate-release kinetics properties, represent good models to be taken into account as systems of controlled drug release.